Strategi Bauran Komunikasi Pemasaran Produk Alam Sari dalam Menarik Perhatian Konsumen - Alyaa Nazala Awwalia; Aning Sofyan (Bandung Conference Series: Communication Management, 2023)
Abstract. Intense competition in the business world requires MSMEs (micro, small and medium enterprises) to survive. One of them is by implementing the right marketing communication mix strategy in attracting the attention of consumers. This research examines how the marketing communication mix strategy is implemented by one of the SMEs (micro, small and medium enterprises) in Subang Regency, namely Alam Sari. This research uses a type of qualitative research with a descriptive study approach. Data collection techniques using interviews, documentation, observation, and literature study. Data analysis techniques in three ways, namely data reduction, data presentation, and drawing conclusions. To test the validity of the data in this study using source triangulation and technique triangulation. Meanwhile, the theory used in this research is integrated marketing communication (IMC) theory. The results of this study indicate that to face competition between MSMEs (micro, small and medium enterprises), Alam Sari implements several marketing communication strategies including advertising or advertising through digital media such as WhatsApp and Instagram social media as well as marketplaces, Shopee and Tokopedia. Sales promotion or sales promotion by giving bonuses and product samples. Personal selling or personal selling by providing good service and approach to consumers and frequently participating in trade shows. Finally, public relations or public relations by empowering the surrounding community, such as providing opportunities for the surrounding community to take part and help pineapple farmers, as well as publication activities by mass media such as the NOVA e-magazine, Trans 7 and Trans TV television media, and Bank BRI. Abstrak. Persaingan yang ketat dalam dunia bisnis menuntut UMKM (usaha mikro, kecil, dan menengah) untuk tetap bertahan. Salah satunya dengan menerapakan strategi bauran komunikasi pemasaran yang tepat dalam menarik perhatian konsumen. Penelitian ini meneliti mengenai bagaimana strategi bauran komunikasi pemasaran yang diterapkan oleh salah satu UMKM (usaha mikro, kecil, dan menengah) Kabupaten Subang yaitu Alam Sari. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan studi deskriptif. Teknik pengumpulan data menggunakan wawancara, dokumentasi, observasi, dan studi kepustakaan. Teknik analisis data melalui tiga cara yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Untuk menguji keabsahan data pada penelitian ini menggunakan triangulasi sumber dan triangulasi teknik. Sedangkan teori yang digunakan dalam penelitian ini adalah teori integrated marketing communicatin (IMC). Hasil pada penelitian ini menunjukkan bahwa Untuk menghadapi persaingan antar UMKM (usaha mikro, kecil, dan menengah), Alam Sari mengimplementasikan beberapa strategi buaran komunikasi pemasaran diantaranya advertising atau periklanan melalui media digital seperti media sosial whatsapp dan instagram serta marketplace shopee dan tokopedia. Sales promotion atau promosi penjualan dengan memberikan bonus dan sampel produk. Personal selling atau penjualan personal dengan memberikan pelayanan dan pendekatan yang baik kepada konsumen dan sering mengikuti pameran dagang. Terakhir public relation atau hubungan masyarakat dengan memberdayakan masyarakat sekitar seperti memberikan kesempatan masyarakat sekitar untuk ikut andil dan membantu petani nanas, serta kegiatan publikasi oleh media massa seperti e-magazine NOVA, media televisi Trans 7 dan Trans TV, dan Bank BRI.